TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN KULIAH DARING BERBASIS UBIQUITOUS LEARNING DI TENGAH PANDEMIC COVID – 19 (STUDI KASUS :MAHASISWA STIKOM UYELINDO KUPANG) - Iriane, Gregorius Rinduh; Katemba, Petrus (HOAQ (High Education of Organization Archive Quality) : Jurnal Teknologi Informasi, 2020)
One of the serious problems faced by the Institute of Higher Education, STIKOM Uyelindo Kupang in early 2020 was the replacement of the Corona Virus Covid-19 outbreak which involved all academic activities that were canceled and put into effect online teaching and learning processes or online lectures. Online lectures or online-based lecture systems also called e-learning or Online Courses are lecture processes using information and communication technology in this case the internet. Digital-based learning has been developed from E-Learning to M-Learning to U-Learning and to S-Learning or Smart Learning. The method of learning everywhere without difficulty by space and time has become important and breakthroughs in the field of education are often referred to as Ubiquitous Learning. Learning everywhere or U-Learning is a learning technology that can be carried out anywhere and at any time by integrating mobile technology as a supporting tool. an event, impact or things that cause changes to the process that is happening. The results of this study found out the level of student satisfaction with online lecture services based on ubiquitous learning at STIKOM Uyelindo Kupang